Strategi Manajemen Pemasaran E-Commerce Dhinda Hijab - Altifianuri, Fazrilhiani; Insani, Galang Habib; Khaeriyah, Khaeriyah; Fahmi, Ilham; Ulya, Neng (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of the research conducted was to provide experience and knowledge by means of case studies of Dhinda Hijab stores in e-commerce. The approach and method carried out by the research is to use qualitative descriptive. Data sources obtained through empirical data, case studies, observations, and interviews. Data analysis is carried out through data reduction, data presentation, and conclusion drawing. The results of the research obtained by the e-commerce marketing strategy applied in Dhinda Hijab are the strategy of Upselling products, promotions, discounts, photos or with complete video content. The impact of e-commerce provides many conveniences that are reached such as; facilitating digital product promotion, reaching more customers, and services in customer satisfaction